Pengembangan Sistem Informasi Akreditasi LAM INFOKOM Berbasis Web dengan Workflow Management untuk Meningkatkan Efektivitas Pengelolaan Dokumen Akreditasi - Anjar Pinem (Jurnal Manajemen Informatika Medicom (JMI), 2026)
The digitalization of accreditation processes is an urgent need for higher education institutions to enhance efficiency and transparency. This research aims to develop a web-based accreditation information system for LAM INFOKOM that integrates workflow management to address the complex and often ineffective issues of accreditation document management. The system is designed using the Design Science Research (DSR) methodology, encompassing problem identification, requirements gathering, workflow design, database design, system design, implementation using the Laravel framework, and testing based on ISO/IEC 25010 standards. The results indicate that the developed system can automate the accreditation workflow, from cycle creation, PIC assignment, document upload, validation, review, to approval, while providing real-time monitoring and audit trails. The implementation of this system is expected to improve the effectiveness of accreditation document management, reduce the risk of document loss, and enhance the transparency of the accreditation process.